Carnival festivities in post-independence Brazil - Leal, Caroline (2023)
This article seeks to relate the political emancipation of Brazil, which took place in 1822, and the attempts to eliminate Entrudo as a practice of Carnival commemoration, which began to manifest itself from the end of that decade. From the analysis of a diversified set of documents, which includes travellers’ reports, newspapers, literary works and official documents, such as municipal decrees, permits, laws and decrees, we work with the hypothesis that the Entrudo persecution it would also be the rejection of a Portuguese identity and the search for a “Brazilianness”, based on the ideal of civilization, along the lines of other European nations.